MICROSATELLITE MARKERS DEVELOPED FOR UTRICULARIA RENIFORMIS (LENTIBULARIACEAE) - Clivati, Debora; Gitzendanner, Matthew Aaron; Silva Hilsdorf, Alexandre Wagner; Araujo, Welington Luiz; Oliveira de Miranda, Vitor Fernandes [UNESP] (Botanical Soc Amer Inc, 2012)
Premise of the study: Microsatellite markers were developed to study the genetic diversity and population structure of the carnivorous bladderwort Utricularia reniformis, which is endemic to the Atlantic Forest of southern and southeastern Brazil. Cross-species amplification was tested in U. gibba, U. neottioides, U. subulata, and Pinguicula benedicta.Methods and Results: The U. reniformis genome was sequenced in a 454 GS FLX sequencer, and eight primer sets were developed based on the microsatellites identified from the reads. All loci are polymorphic, showing 1.6 to 4.8 alleles per population. Preliminary results show that primer sets are suitable for population-level studies. Cross-species amplifi cation was successful in three other Utricularia species and one Pinguicula species.Conclusions: Markers developed in this study provide tools for analyses of intra- and interpopulation genetic diversity in Utricularia and Pinguicula.
Keywords: Atlantic Forest; bladderworts; endemic plants; genetic diversity; Lentibulariaceae; Utricularia reniformis